(untitled) (The Pakistan Development Review, 2000)
The issue of how developing countries can accelerate their economic growth is of crucial importance. The two primary alternative routes to development are inward-oriented growth strategies, which emphasises import-substitution industrialisation (ISI); and outward-oriented policies, which emphasises the economic benefits of participation in the world economy, that is, export-led growth (ELG). The late 1960s and 1970s witnessed a disillusionment with ISI in many developing countries, leading to a reduction in protectionist measures. The 1980s witnessed further intensification of liberalisation measures as many countries retreated from socialism, regulation and planning. The dis-advantages of ISI, the potential strength of ELG policies and the conditions necessary for successful transition from an inwardoriented regimes to an outward oriented have been extensively researched1 and beyond the scope of the present study. Moreover many of the rapidly growing newly industrialising countries (NICs) lend support to the idea that export promotion can be an effective development strategy. Naturally such a line of causation is consistent with macroeconomic theory, where exports are treated as injections into the economy [Kaldor (1967); Feder (1982); Romer (1989); Krueger (1990) and Marin (1992)]